RANCANG BANGUN SISTEM KONTROL LAMPU, PAGAR, PINTU, DAN JENDELA (LPPJ) PADA MINIATUR RUMAH MENGGUNAKAN ARDUINO DAN TELEPON SELULE - Aziz, Fariz Abdul; Sumariyah, Sumariyah (BERKALA FISIKA, 2020)
The positive impact of technological advancements is to make it easier to use and to control electronic devices by a microcontroller. The aim of this research is to remotely control lights, fences, doors, and windows (LPPJ) on miniature homes using cellular phones connected to bluetooth using Arduino Mega 2560. This control system consisted of Arduino Mega 2560, LDR sensor, servo motor and motor servo2, DC motors, relays, and cellular phones. The workings of the LPPJ control system is when the LDR sensor detects sunlight, then it will give an order to the relay to turn on or off the light. In addition to using the LDR sensor to control the lights, the LPPJ system uses remote control by using cellular phones with communication via Bluetooth to turn on or off the light, to move the fence, door, and window by pressing the button on the cellphone. It is successfully designed and developed a control system of LPPJ on miniature homes using the cellular phones.